DETERMINAN PARTISIPASI SEKOLAH ANAK DI INDONESIA - Rafly Firmansyah; Muhammad Abdul Ghofur (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Education is an important factor for improving the quality of human resources, currently there are problems with education in Indonesia which cause education to still not run optimally, this research aims to analyze the influence of the poverty level (X1), the number of teachers (X2), and the number of schools ( X3) on school enrollment rates. Secondary data was obtained from the bps.go.id website taking data from 34 provinces with a time interval from 2018-2022, using quantitative methods and panel data regression approaches using the Eviews 10 application. The results of this study show that the poverty level has no effect on school enrollment rates , while the number of teachers and number of schools have an influence on school enrollment rates. The practical implication of this research is that the government can choose areas that are still far from equal distribution of school unit facilities and teachers because school enrollment rates are influenced by capacity and adequate school facilities. For researchers with related titles, it is hoped that they will add an education budget variable because the education budget supports school facilities in Indonesia.Key words: school enrollment rate, poverty level, number of teachers, number of schools